2009
DOI: 10.1021/np800808h
|View full text |Cite
|
Sign up to set email alerts
|

Hirseins A and B, Daphnane Diterpenoids from Thymelaea hirsuta That Inhibit Melanogenesis in B16 Melanoma Cells

Abstract: Two new daphnane diterpenoids, hirseins A (1) and B (2), were isolated from the aerial parts of Thymelaea hirsuta, and their structures were elucidated on the basis of spectroscopic data interpretation. Hirsein B (2) is an unusual daphnane in possessing a coumaroyl moiety. NOESY correlations of 2 implied that isomerization of the coumaroyl group in 2 was caused by equilibrium between the E (2e) and Z (2z) forms. Compounds 1 and 2 were found to inhibit melanogenesis in B16 murine melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Hence, we cannot explain the detailed pathway involved in MITF repression by the inhibitors. These inhibitors include 2-amino-3 H -phenoxazin-3-one (Figure 6a) from the mushroom Agaricus bisporus [61], myrtenol 10-O-[β- d -apiofuranosyl-(1→6)-β- d -glucopyranoside] (Figure 6b) from the leaves of Momordica charantia [62], lucidone (Figure 6c) from the fruits of Lindera erythrocarpa [63], anemonin (Figure 6d) from the leaves of Clematis crassifolia [64], hirsein A (Figure 6e) and hirsein B (Figure 6f) from the leaves of Thymelaea hirsuta [65,66], 7-(4''-hydroxy-3''-methoxyphenyl)-1-phenylhept-4-en-3-one (Figure 6g), kaempferide (Figure 6h), and galangin (Figure 6i) from the rhizomes of Alpinia officinarum [67], and vanillic acid (Figure 6j) [68], origanoside (Figure 6k) [69], and protocatechuic acid (Figure 6l) [70] from Origanum vulgare . Despite there being no detailed explanation for the mechanism regarding MITF inhibition by the inhibitors, vanillic acid and origanoside both show excellent hypopigmentation activity in in vivo mice systems and are good candidates in skin-whitening cosmetics applications.…”
Section: Natural Melanogenesis Inhibitors Acting Through the Down-mentioning
confidence: 99%
“…Hence, we cannot explain the detailed pathway involved in MITF repression by the inhibitors. These inhibitors include 2-amino-3 H -phenoxazin-3-one (Figure 6a) from the mushroom Agaricus bisporus [61], myrtenol 10-O-[β- d -apiofuranosyl-(1→6)-β- d -glucopyranoside] (Figure 6b) from the leaves of Momordica charantia [62], lucidone (Figure 6c) from the fruits of Lindera erythrocarpa [63], anemonin (Figure 6d) from the leaves of Clematis crassifolia [64], hirsein A (Figure 6e) and hirsein B (Figure 6f) from the leaves of Thymelaea hirsuta [65,66], 7-(4''-hydroxy-3''-methoxyphenyl)-1-phenylhept-4-en-3-one (Figure 6g), kaempferide (Figure 6h), and galangin (Figure 6i) from the rhizomes of Alpinia officinarum [67], and vanillic acid (Figure 6j) [68], origanoside (Figure 6k) [69], and protocatechuic acid (Figure 6l) [70] from Origanum vulgare . Despite there being no detailed explanation for the mechanism regarding MITF inhibition by the inhibitors, vanillic acid and origanoside both show excellent hypopigmentation activity in in vivo mice systems and are good candidates in skin-whitening cosmetics applications.…”
Section: Natural Melanogenesis Inhibitors Acting Through the Down-mentioning
confidence: 99%
“…The leaves decoction is used in folk medicine to treat skin diseases and abdominal pain (Boukef 1986 Thymelaea genus (Thymelaea hirsuta Endl.) is traditionally used for its several and welldocumented antiseptic, anti-inflammatory, antimelanogenesis and antihypertensive properties (Miyamae et al 2009;Akrout et al 2011;Trigui et al 2013;Amari et al 2014). Furthermore, the antioxidant properties of its aerial parts have recently been investigated (Amari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that one fraction of T. hirsuta considerably decreased melanin synthesis in B16 cells and that the main components of this fraction are daphnanes. Two new daphnane diterpenoids, namely hirsein A and hirsein B, were isolated from the aerial parts of T. hirsuta and were found to inhibit melanogenesis in B16 murine melanoma cells 13 …”
Section: Discussionmentioning
confidence: 99%